1985
DOI: 10.1021/bi00345a002
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced increase in the radius of gyration and maximum dimension of calmodulin measured by small-angle x-ray scattering

Abstract: We have used solution small-angle X-ray scattering to characterize bovine brain calmodulin in the presence and absence of calcium. In the presence of calcium, calmodulin exists in solution as an elongated molecule with a radius of gyration of 21.5 A and a maximum vector length of approximately 62 A. These values are consistent with the dimensions recently determined for the crystal form of rat testis calmodulin. In the absence of calcium, the calmodulin molecule is shorter, the radius of gyration decreases to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
117
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(137 citation statements)
references
References 18 publications
19
117
1
Order By: Relevance
“…This changes the overall conformation of the protein from the extended structure of apoCaM to the more extended characteristic dumbbell shape of Ca 2+ CaM. This increase in radius of gyration (R g ) of the protein was observed in small-angle X-ray scattering (SAXS) studies (Seaton et al, 1985;Heidorn et al, 1989;Matsushima et al, 1989Matsushima et al, , 2000.…”
Section: Introductionmentioning
confidence: 93%
“…This changes the overall conformation of the protein from the extended structure of apoCaM to the more extended characteristic dumbbell shape of Ca 2+ CaM. This increase in radius of gyration (R g ) of the protein was observed in small-angle X-ray scattering (SAXS) studies (Seaton et al, 1985;Heidorn et al, 1989;Matsushima et al, 1989Matsushima et al, , 2000.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, incorporation of Tyr-138 into the exiting a-helix of site 4 has been shown to be a calcium-induced event (Kuboniwa et al, 1995) One possible mechanism whereby N-terminal calcium binding might affect Tyr-138 is by direct interaction between the two terminal lobes of the protein. However, although the two lobes can approach more closely in solution than indicated by the crystal structure (Seaton et al, 1985;Heidorn & Trewhella, 1988), no NOE interactions are detected between side chains located in opposing terminal lobes of calmodulin in either the apo-or the holo-form of the protein (Ikuraet al, 1991). Therefore, on the time scale detected by NMR, no residues of the N-terminus are within 5 A of any C-terminal residues, suggesting that direct interaction between the two terminal lobes is unlikely.…”
Section: Analysis In Terms Of the Known Properties Of Tyr-138mentioning
confidence: 99%
“…SAXS analysis has indicated that the terminal lobes of the protein are maintained in the absence of calcium, but are closer together by about 5 A (Seaton et al, 1985;Heidorn & Trewhella, 1988). Nevertheless, biophysical and biochemical studies with both the intact protein and the separated N-and C-terminal halves have suggested that the calcium-induced conformational changes in the two terminal lobes are independent of one another (Forsen et al, 1986;Martin & Bayley, 1986).…”
mentioning
confidence: 99%
“…Given the effects of electrolytes on the electrical measurements taken by a SiNW-FET, we generally used phosphate solution (0.1 × PS, consisting of 0.76 mM Na 2 HPO 4 and 0.24 mM NaH 2 PO 4 at pH 7.4) as a buffer in all of the sensing experiments, of which the corresponding Debye screening length (λ D ) is 6.1 nm. The electrical measurements under such a solution environment should effectively reflect the binding of interacting proteins to CaM-GST that was estimated to be ∼5.6 nm distant from the surface of the SiNW-FET (17,18). As shown in Fig.…”
Section: Supporting Information)mentioning
confidence: 99%